Reducing prescribing costs through computer controlled repeat prescribing - Difford, Frederick (1984)
A small reduction in prescribing costs is reported from a general practice that has been using a computer for repeat prescribing for three years. The possible reasons for this are discussed. The information available from the Prescription Pricing Authority (PPA) and from practice workload measurements was found to be inconclusive. An elaboration of the computer-controlled system of repeat prescribing to provide a detailed cost analysis of this aspect of prescribing was devised, and the first results are presented. It is calculated that 27 per cent of prescriptions in the practice are produced from electronic records and that the average cost of these is not significantly greater than for prescriptions issued in other situations.